2008
DOI: 10.1016/j.athoracsur.2008.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Link Toll-Like Receptor 4 Signaling to Cardiac Dysfunction After Global Myocardial Ischemia

Abstract: Background-Although Toll-like receptor 4 (TLR4) has been implicated in the myocardial injury caused by regional ischemia/reperfusion, its role in the myocardial inflammatory response and in contractile dysfunction after global ischemia/reperfusion is unclear. Cytokines, particularly tumor necrosis factor-α (TNF-α), contribute to the mechanism of myocardial dysfunction after global ischemia/reperfusion. We hypothesized that a TLR4-mediated cytokine cascade modulates myocardial contractile function after global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…The medical management of the more severe cases of cardiac ischemia is often inadequate, thereby warranting revascularization via percutaneous stenting or arterial bypass. The subsequent reperfusion injury associated with the ischemic episode is also detrimental and results in significant aberrations to the inflammatory cascade (3,8,22). In this regard, bone marrow mesenchymal stem cells (MSCs) represent a novel treatment modality with increasing therapeutic potential (1,12,17,23,27).…”
Section: Ischemia-reperfusionmentioning
confidence: 99%
“…The medical management of the more severe cases of cardiac ischemia is often inadequate, thereby warranting revascularization via percutaneous stenting or arterial bypass. The subsequent reperfusion injury associated with the ischemic episode is also detrimental and results in significant aberrations to the inflammatory cascade (3,8,22). In this regard, bone marrow mesenchymal stem cells (MSCs) represent a novel treatment modality with increasing therapeutic potential (1,12,17,23,27).…”
Section: Ischemia-reperfusionmentioning
confidence: 99%
“…In mice treated with the TLR4 antagonist eritoran, myocardial mRNA levels of TNF-␣, IL-1␤, and IL-6 were significantly reduced after regional ischemia-reperfusion (26). In a mouse model of isolated global myocardial ischemia-reperfusion, defective TLR4 was associated with reduced myocardial production of TNF-␣ and IL-1␤ peptides and attenuated postischemic cardiac dysfunction (5). These studies link TLR4 signaling to the postischemic myocardial inflammatory response and cardiac dysfunction, but it remains unclear how TLR4 is activated during myocardial ischemia-reperfusion.…”
mentioning
confidence: 91%
“…to regional I/R (21,22) and global I/R (16,23). Our previous studies found that TLR4, particularly myocardial tissue TLR4, plays a major role in mediating myocardial expression of proinflammatory mediators in response to global I/R (16,24).…”
Section: Attenuated Recovery Of Contractile Function In Aging Heartsmentioning
confidence: 99%
“…Our previous studies found that TLR4, particularly myocardial tissue TLR4, plays a major role in mediating myocardial expression of proinflammatory mediators in response to global I/R (16,24). Furthermore, cardiodepressant cytokines TNF-α and IL-1β link TLR4 to postischemic cardiac dysfunction (16).…”
Section: Attenuated Recovery Of Contractile Function In Aging Heartsmentioning
confidence: 99%
See 1 more Smart Citation